Faktor yang Berhubungan dengan Pemberian ASI Eksklusif di Puskesmas Perumnas Kecamatan Lahat Kabupaten Lahat - Yopi Handayani; Siti Aisyah; Satra Yunola (Jurnal Kesehatan Saelmakers PERDANA, 2023)
World Health Organization (WHO) recommends that the best way to keep babies and mother health is to give exclusive breastfeeding at least to 6 months. The World Allience for Breastfeeding Action (WABA) estimates that 1 million babies might be safe every year if they have breast-milk at the first 1 hour of birth then continue with exclusive breast-milk until 6 months, because breast-milk not only contains enough nutrition, but complete, and it also has immune that useful to the immunity of the baby. There is only 64.7% breastfeeding mothers in the world that did exclusive breastfeeding. The method used in this study was analytic survey with cross sectional approach. The statistical test was chi-square test. The population of this study was women who owned baby with age more than 6 months at Perumnas Public Health Center, Lahat District 2021 which was estimated to be 380 respondents and the sample was 79 respondents. The univariate analysis showed that of 79 respondents studied, there was 27 respondents (34.2%) did exclusive breastfeeding, whose with good knowledge was 21 respondents (26.6%), whose with working was 16 respondents (20.3%), and whose with husband well support was 30 respondents (38.0%). The result showed that there was significant relationship between knowledge and exclusive breastfeeding p value 0.004 <? = 0.05, there was significant relationship between work and exclusive breastfeeding p value = 0.017 <? = 0.05, and there was significant relationship between husband support and exclusive breastfeeding p value = 0.010 <? = 0.05. The results of this study are expected to increase exclusive breastfeeding on mothers with 0-6 month baby.